Penguasaan Wilayah Oleh Pemberontak dan Implikasi Hukum terhadap Hak Asasi Manusia - Gremy Marsel Makatita; Lucia Charlota Octovina Tahamata; Popi Tuhulele (TATOHI: Jurnal Ilmu Hukum, 2022)
Introductioan: In fact, what happened in Afghanistan shows that the protection of civilians is not fully guaranteed, and the existing regulations on insurgency and armed conflict have always been entirely by the parties to the insurgency and conflict, indicating that it has not been implemented.Purposes of the Research: This writing aims to analyze and find out international law governing the control of territory by rebels and the legal implications of territorial control by rebels on human rights.Methods of the Research: The type of research used is normative, which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. The processing and analysis of legal materials is described in a qualitative way with the aim of describing the findings in the field.Results of the Research: Provisions regarding non-international armed conflicts / rebels are regulated only based on Article 3 of the General Articles of the 1949 Geneva Conventions and Additional Protocol II of 1977. There are several conditions that must be met in order for a rebel group to be recognized as belligerent and become a subject in international law. The legal implications of the Taliban's territorial control in relation to hostilities affect not only members of the military but also civilians. Moreover, as the weak and suffering party, civilians are easily the targets of violence with various false claims. Humanitarian law also regulates the protection of the civilian population in Article 27 of Convention IV of 1949. The government or state is obliged to fully enforce the law to protect those who are victims of violations of international humanitarian law. To protect human rights in various situations, legal means are needed to create legal certainty in the implementation of the protection of everyone's rights.